Prospectively measured levels of serum follicle-stimulating hormone, estradiol, and the dimeric inhibins during the menopausal transition in a population-based cohort of women - Burger, H G; Dudley, E C; Hopper, J L; Groome, N; Guthrie, J R; Green, A; Dennerstein, L (The journal of clinical endocrinology and metabolism, 1999)
The aims of this study were: 1) to describe, in relation to the date of final menses, the average hormone levels of women in the years before and after this date and to determine the extent to which these average levels were dependent on age and body mass index (BMI); and 2) to determine the degree of tracking in residual hormone levels [i.e., the extent to which individuals above (below) the mean for their age or time relative to final menstrual period (FMP) and BMI remain above (below) the mean as time progresses]. Serial levels of serum FSH, circulating estradiol (E2), and the dimeric inhibins (INH) A and B were measured annually in 150 women who experienced a natural menopause during 6 years of follow-up. Means of the log-transformed hormonal levels were analyzed as a double-logistic function of time relative to FMP, as well as age and BMI and correlations between repeated hormonal levels, were measured. Mean FSH levels started to increase from about 2 years before the FMP, increased most rapidly about 10 months before the FMP, and had virtually plateaued by 2 years after the FMP. FSH levels were, on average, 3% greater for each year of age and 2% lower for each kg/m2 of BMI. After adjusting for time relative to the FMP, logFSH showed modest tracking. Age-adjusted values of logFSH were moderately correlated across time, and much of this tracking was explained by the actual timing of a woman's FMP. Mean E2 levels started to decrease about 2 years before the FMP, decreased most rapidly around the time of the FMP, and had virtually plateaued by 2 years after the FMP. E2 levels were lower, on average, by about 9% per year of age, and residual values showed weak tracking. Levels of both INHA and INHB decreased, on average, in the years before the FMP and were undetectable (INHA, < 10 pg/mL; INHB, < 25 pg/mL) in the majority of women by the time of the FMP and in almost all women by 4 years post-FMP. Significant negative correlations between log serum FSH and log E2 (r = -0.73) and log INHA (r = -0.41) and log INHB (r = -0.36) were observed. It is concluded that substantial changes in reproductive hormone levels occur within 1-2 yr on each side of the FMP, that falling concentrations of E2 and the INH contribute to the rising concentrations of FSH, and that there is no single reliable hormonal marker of menopausal status for an individual woman.